Clinical Efficacy of Endoscopic Treatment for Benign Colorectal Stricture: Balloon Dilatation versus Stenting - Park, Chan Hyuk (Gut Liver, 2015)
BACKGROUND/AIMS: There has been a lack of research comparing balloon dilatation and self-expandable metal stent (SEMS) placement to determine which is better for long-term clinical outcomes in patients with benign colorectal strictures. We aimed to compare the clinical efficacy and complication rates of balloon dilatation and SEMS placement for benign colorectal strictures from a variety of causes. METHODS: Between January 1999 and January 2012, a total of 43 consecutive patients who underwent endoscopic treatment for benign colorectal stricture (balloon only in 29 patients, SEMS only in seven patients, and both procedures in seven patients) were retrospectively reviewed. RESULTS: Thirty-six patients underwent endoscopic balloon dilatation, representing 65 individual sessions, and 14 patients received a total of 17 SEMS placements. The initial clinical success rates were similar in both groups (balloon vs SEMS, 89.1% vs 87.5%). Although the reobstruction rates were similar in both groups (balloon vs SEMS, 54.4% vs. 57.1%), the duration of patency was significantly longer in the balloon dilatation group compared with the SEMS group (65.5±13.3 months vs. 2.0±0.6 months, p=0.031). CONCLUSIONS: Endoscopic balloon dilatation is safe and effective as an initial treatment for benign colorectal stricture and as an alternative treatment for recurrent strictures.